2002
DOI: 10.1016/s0886-3350(01)01103-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a ray-tracing refractometer, autorefractor, and computerized videokeratography in measuring pseudophakic eyes

Abstract: Spherical and cylindrical refractive data obtained with the Tracey system correlated well with those derived from MR; however, there was a mean spherical error of approximately 1.10 D. Further work is required to refine the accuracy and range of this device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 15 publications
1
21
0
4
Order By: Relevance
“…In addition, it can achieve a high sampling rate even with small pupils because the number of spots does not depend on the pupil size. 3,9,16 On the other hand, this nonconstant spot separation also results in lower resolution for larger pupils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it can achieve a high sampling rate even with small pupils because the number of spots does not depend on the pupil size. 3,9,16 On the other hand, this nonconstant spot separation also results in lower resolution for larger pupils.…”
Section: Discussionmentioning
confidence: 99%
“…A good correlation between refractive data obtained with the device and subjective manifest refraction has been shown. 9 The subjects fixated on targets through the viewing path of the aberrometer. Because variations in the subjects' line of sight could cause off-axis readings and lead to differences in measurement results, 4,10 an elongated target holder was installed on top of the instrument to ensure carefully aligned near targets at 0.4 to 1.0 m (2.5 to 1.0 D) ( Figure 1).…”
Section: Measurement Proceduresmentioning
confidence: 99%
“…The device projects 64 light rays in programmable scan pattern (in default on four concentric circles) across the pupil in succession and detects the retinal location of reflection with the help of two linear charged coupled device (CCD) arrays. 13,14 On the basis of these measurements, the device calculates the retinal point spread function and subsequently the wavefront aberrations. In default setting of automatic mode, it scans at the largest possible pupil area and displays wavefront data.…”
Section: Instrumentsmentioning
confidence: 99%
“…There have been several other studies of wavefront measurement device reproducibility. 13,14,22 These have included the Tracey device and the WaveScan system (VISX, Santa Clara, CA, USA) as well as a method using Hartmann-Shack techniques. These studies found that the standard deviation of the conventional refractive index measured by wavefront devices was between 0.1 and 0.5D.…”
Section: Comparison Of Two Wavefront Devices D-ug Bartsch Et Almentioning
confidence: 99%
“…As aberrações ópticas, neste estudo, foram medidas com o aberrômetro Zywave ® que utiliza o sensor de Hartmann-Shack, o qual mede as aberrações oculares totais. Outros videoceratoscópios computadorizados podem medir a forma corneana, desenhar mapas de elevação e realizar a decomposição polinomial que é utilizada para determinar as aberrações cornea- nas (15)(16) . O conhecimento das aberrações de frentes de onda corneana e lenticular é essencial para o entendimento da natureza de cada aberração e para sua correção.…”
Section: Biomedicsunclassified